Where the money is [videorecording (DVD)] - Kanievska, Marek; Newman, Paul, 1925-2008; Fiorentino, Linda; Mulroney, Dermot (Universal : USA Home Entertainment, 2000)
A veteran thief faking a stroke, his very sexy nurse and her earnest, boring husband are going after money. All they have to do is steal an armored truck, impersonate the guards, collect bags of cash at the pick-up sites and then show up for work the next morning as if nothing happened!